Sex-dependent association between angiotensin-converting enzyme insertion/deletion polymorphism and obesity in relation to sodium intake in children - Yang, Soo Jin; Kim, Sunyoung; Park, Hyesoon; Kim, Seon-Mee; Choi, Kyung-Mook; Lim, Yunsook; Lee, Myoungsook (Nutrition (Burbank, Los Angeles County, Calif.), 2013)
Obesity is a complex condition that is influenced by genetic and environmental factors and is associated with an increased risk for diabetes, hypertension, and cardiovascular diseases. Angiotensin-converting enzyme (ACE) is well characterized in the control of blood pressure. This study investigated whether the ACE insertion/deletion (I/D) polymorphism affects obesity in relation to sodium intake in children. A cross-sectional study was conducted in 1260 elementary schoolchildren (633 boys and 627 girls). Subjects were assessed for the degree of obesity, sodium intake, and ACE I/D genotype, and associations were evaluated between the ACE I/D polymorphism and obesity in relation to sodium intake. Sodium intake was significantly correlated with the obesity index (r = 0.048, P = 0.016) and was particularly high in obese D-carrier boys compared with normal D-carrier boys. D-carrier boys did not show any association with the degree of obesity, whereas D-carrier girls with a high sodium intake exhibited a significant association (odds ratio 0.551, P = 0.042) and a negative correlation between the D allele and obesity as a continuous variable (regression coefficient −3.095, P = 0.020), showing gender-dependent associations between the ACE I/D polymorphism and obesity in relation to sodium intake. These findings demonstrate that the association between the ACE I/D polymorphism and obesity in relation to sodium intake is gender dependent in children.